A Feminist Approach to Immigrant Admissions. (2017) - Higgins, Peter
Abstract : Answers to the question of immigrant admissions (what policies governing the admission and exclusion of nonrefugee foreigners may states justly adopt?) have been debated extensively by political philosophers since the 1980s. A wide variety of normative approaches to the question have been taken, but very nearly zero have been expressly feminist. Generalizing from Alison Jaggar's articulation of a feminist methodological approach to the political morality of abortion, this article proposes a feminist methodological approach to immigrant admissions. This article does not defend a substantive view on what policies states ought to adopt, but it does describe several features of our social world that are salient for a feminist methodological approach to the assessment of the justice of states' immigrant admissions policies.